Effect of dip wash treatments with organic acids and acidic electrolyzed water combined with ultraviolet irradiation on quality of strawberry fruit during storage - Nour,Violeta (2021)
ABSTRACT The objective of this study was to determine the effects of dip wash treatments with 2% citric acid (CA), 0.2% benzoic acid (BA), 0.2% sorbic acid (SA) and acidic electrolyzed water (AEW) followed by 2 kJ·m–2 ultraviolet (UV) irradiation on the postharvest decay and quality of strawberry fruit cultivar ‘Malvina’, as compared to control, and UV alone treated samples. Weight loss, firmness, soluble solids content, titratable acidity, total phenolics content, total anthocyanins content, antioxidant activity and decay incidence of control and treated strawberry fruits were investigated during cold storage at 8 °C for 21 days. The result showed that UV-treated fruits had a lower weight loss, higher titratable acidity, phenolic and anthocyanin content and were firmer than the untreated fruits. Dip wash in AEW before UVC treatment reduced weight loss and increased firmness of strawberry fruits but did not significantly affect total phenolic content, total anthocyanins content, 2,2-diphenyl-1-picrylhydrazyl (DPPH) antioxidant activity and fruit decay. Dip wash treatment with organic acids followed by UVC irradiation was significantly more effective than UV treatment alone in reducing fruit decay and weight loss and in maintaining at higher levels titratable acidity, total anthocyanins content, total phenolic content and antioxidant activity of strawberries during refrigerated storage. The present findings demonstrate that dip wash treatment with 0.2% SA, 0.2% BA or 2% CA followed by UV treatment can be an effective method for maintaining the phytochemical content and delaying the decay of strawberry fruit during cold storage.